Clinical and anamnestic risk factors for the development of uterine leiomyoma in women of reproductive age: A case control study - Darya A. Malyshkina; Nataliya Yu. Sotnikova; Dmitriy N. Voronin; Arina E. Kalinina; Elizaveta M. Godunova; Maria V. Golubeva; Elizaveta V. Rumyanceva (IP Berlin A.V., 2023)
Aim. To identify risk factors for uterine leiomyoma (ULM) in women of reproductive age based on the study of clinical and medical history features in various tumor types. Materials and methods. The study included 82 women of reproductive age with symptomatic ULM (the main group) and 47 somatically healthy women of reproductive age without proliferative gynecological diseases who underwent elective treatment at the Gorodkov Ivanovo Research Institute of Motherhood and Childhood (Director is professor AI Malyshkina, MD, Ph.D.). The study patients underwent general clinical examinations, ultrasound examination of the pelvic organs, histological examination of endometrial biopsy specimens, and myomatous nodes in women of the main group. Results. The following risk factors and clinical and history features were identified in women with uterine fibroids: late reproductive age (p=0.000), unregistered marriage (p=0.026), employment (p=0.006), history of profuse and painful menstruation (p=0.000 and p=0.000, respectively), inflammatory diseases of the respiratory system (p=0.003), pain syndrome and profuse menstruation (p=0.000 and p=0.000, respectively), endometrial hyperplasia without atypia, and chronic endometritis according to histological examination (p=0.000 and p=0.000, respectively). When comparing the subgroups "Ki67+" and "Ki67-", we obtained the following clinical and history features in women with proliferating uterine fibroids: varicose disease of the lower extremities (p=0.035); and when comparing the subgroups "with secondary changes" and "without secondary changes", we found a higher rate of pain (p=0.038) in women with secondary changes in the myomatous node, as well as a tendency to a higher rate of painful menstruation (p=0.093) and endometrial hyperplasia (p=0.093). Conclusion. Risk factors for ULM in women of reproductive age can be divided into modifiable ones, which include social disadvantage (unregistered marriage, hard physical work), inflammatory factor (inflammatory diseases of the respiratory system) and unmodifiable (late reproductive age). Clinical and history features of women with Ki67+ ULM compared to women with Ki67- ULM include more frequent use of barrier contraception, high prevalence of varicose vein disease of the lower extremities, and surgical interventions on the pelvic organs. Also, according to histological examination, women with ULM with secondary changes in the myomatous node, compared to women with ULM without secondary changes in the myomatous node, have a higher prevalence of painful menstruation, pain syndrome, and concomitant endometrial hyperplasia.